PENGARUH MAQASHID SYARIAH DAN EFEKTIVITAS PROGRAM MEC TERHADAP KESEJAHTERAAN MUSTAHIK MELALUI PRODUKTIVITAS KERJA - Romadhani, Karunia; Annisa, Duta; Widiastuti, Tika (Jurnal Ekonomika dan Bisnis Islam, 2024)
This study investigates the effect of maqasid sharia and the effectiveness of the MEC (Mandiri Entrepreneur Center) of LAZ Yatim Mandiri Surabaya program on mustahik welfare through work productivity as an intervening variable. Previously, there were previous studies that discussed the effect of maqasid sharia using qualitative methods. However, the method used in this study is quantitative by distributing questionnaires online and SEM-PLS as an analytical tool. The results showed that the value of maqashid sharia has a significant effect on work productivity and mustahik welfare. In contrast, the effectiveness of the MEC program has no effect on work productivity and mustahik welfare. Furthermore, work productivity is proven to be significant as an intervening variable that mediates the maqasid sharia principle in influencing mustahik welfare. In conclusion, a maqasid sharia-oriented approach has an important role in improving the welfare of mustahik through increased work productivity. Therefore, the integration of ethical and moral values in economic empowerment programs through zakat can be an effective strategy to improve mustahik welfare and encourage mustahik to transform into muzaki.